Inhibition of the Apparent Rate of Synthesis of the Vacuolar Glycoprotein Carboxypeptidase Y and Its Protein Antigen by Tunicamycin in Saccharomyces cerevisiae - Hasilik, Andrej (1976)
Carboxypeptidase Y from Saccharomyces cerevisiae contains 14% mannose, the only neutral sugar present. An antiserum can be raised in rabbits which reacts with both the protein and the sugar moieties of the enzyme. This antiserum also precipitates yeast invertase and yeast cell wall mannan. Thus carboxypeptidase Y, which is known to be localized in yeast vacuoles, is very probably a mannoprotein. Tunicamycin inhibits the apparent formation of carboxypeptidase Y to a similar extent as that of the externally localized mannoprotein, invertase. No accumulation of an inactive nonglycosylated or partly glycosylated carboxypeptidase Y occurs as determined by the immunoprecipitation technique. Tunicamycin also inhibits the apparent formation of proteinase A, whereas it does not affect the increase in the activities of a number of other enzymes. It is suggested that in the synthesis of glycoproteins there exists a regulatory link between the synthesis of their polypeptide chains and the reactions involved in their glycosylation.